(untitled) (Revista Electrónica REDINE, 2021)
The purpose of this research was to generate reflections to understand the resignification of the curriculum based on pedagogical practice and teacher training in the context of higher education to respond to the demands and demands of curricular innovation in university contexts. The research details how the curriculum is resignified through pedagogical practice, how through it education, culture, society and the educational institution can be transformed; In addition, it addresses the relationship of the resignification of teaching work and the reflective process in action, as well as research from teaching practices, to facilitate the construction of the curriculum from the reality of the social context. Finally, the understanding was reached that the curriculum reads the context, when it reads society and culture, when it raises and rethinks, there education and the curriculum are re-signified, to at the same time re-signify the society drawn in the classroom-teacher -student.